2018
DOI: 10.1155/2018/5607349
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Dyslipidemia with the Extent of Coronary Artery Disease in the Multiethnic Study of Atherosclerosis

Abstract: Background The extent of coronary artery calcium (CAC) improves cardiovascular disease (CVD) risk prediction. The association between common dyslipidemias (combined hyperlipidemia, simple hypercholesterolemia, metabolic Syndrome (MetS), isolated low high-density lipoprotein cholesterol, and isolated hypertriglyceridemia) compared with normolipidemia and the risk of multivessel CAC is underinvestigated. Objectives To determine whether there is an association between common dyslipidemias compared with normolipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
3
18
0
5
Order By: Relevance
“…According to data collected and published by Khan et al, 462 million individuals have been affected by type 2 diabetes mellitus in 2017 (6.28% of the world’s population) [ 1 ]. Diabetes mellitus is a significant risk factor for the development of atherosclerosis [ 2 ], near such risk factors as dyslipidemia [ 3 ], arterial hypertension [ 4 ], poor physical activity [ 5 ], tobacco smoking [ 6 ] and obesity [ 7 ]. Diabetes also significantly increases the risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…According to data collected and published by Khan et al, 462 million individuals have been affected by type 2 diabetes mellitus in 2017 (6.28% of the world’s population) [ 1 ]. Diabetes mellitus is a significant risk factor for the development of atherosclerosis [ 2 ], near such risk factors as dyslipidemia [ 3 ], arterial hypertension [ 4 ], poor physical activity [ 5 ], tobacco smoking [ 6 ] and obesity [ 7 ]. Diabetes also significantly increases the risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…The significant prevalence of low HDL level in our study sample matched multiple studies. Among 68 studies involving >300.000 patients in different age groups, HDL was strongly and inversely related to CV events ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kimak et al [12] showed recently that the main problem of a stable coronary angina patients is not the high concentration of total cholesterol and LDL-C but the progressive increase of chronic inflammation and the accompanying increase in triglycerides and apo B lipoprotein concentration but did not examine correlations between parameters of inflammation and the lipid status. Some CVD outcome studies with triglyceride-lowering agents have produced inconsistent results, meaning that no convincing evidence is available that lowering triglycerides by any approach can reduce mortality [13].…”
Section: Discussionmentioning
confidence: 99%